El Cinco de Mayo : an American tradition - Hayes-Bautista, David E., 1945- (University of California Press, 2012)
"Why is Cinco de Mayo--a holiday commemorating a Mexican victory over the French at Puebla in 1862--so widely celebrated in California and across the United States, when it is scarcely observed in Mexico? As David E. Hayes-Bautista explains, the holiday is not Mexican at all, but rather an American one, created by Latinos in California during the mid-nineteenth century. Hayes-Bautista shows how the meaning of Cinco de Mayo has shifted over time--it embodied immigrant nostalgia in the 1930s, U.S. patriotism during World War II, Chicano Power in the 1960s and 1970s, and commercial intentions in the 1980s and 1990s. Today, it continues to reflect the aspirations of a community that is engaged, empowered, and expanding"--Provided by publisher.